2006
DOI: 10.1111/j.1365-2966.2006.10930.x
|View full text |Cite
|
Sign up to set email alerts
|

The Zurich Extragalactic Bayesian Redshift Analyzer and its first application: COSMOS

Abstract: We present the Zurich Extragalactic Bayesian Redshift Analyzer (zebra). The current version of zebra combines and extends several of the classical approaches to produce accurate photometric redshifts down to faint magnitudes. In particular, zebra uses the template‐fitting approach to produce Maximum Likelihood and Bayesian redshift estimates based on the following points. An automatic iterative technique to correct the original set of galaxy templates to best represent the Spectral Energy Distributions (SEDs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
221
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 254 publications
(224 citation statements)
references
References 24 publications
3
221
0
Order By: Relevance
“…We found that, usually, 3-4 iterations are necessary. In contrast with the method described in Feldmann et al (2006) (in which photometric redshifts can also be used), we only use objects with spectroscopic redshifts to derive the offsets. However, we show later in this section that the spectroscopic sample is sufficient to derive accurate systematic offsets even if it is much smaller than the whole galaxy photometric sample.…”
Section: Correction Of Systematic Offsetsmentioning
confidence: 99%
“…We found that, usually, 3-4 iterations are necessary. In contrast with the method described in Feldmann et al (2006) (in which photometric redshifts can also be used), we only use objects with spectroscopic redshifts to derive the offsets. However, we show later in this section that the spectroscopic sample is sufficient to derive accurate systematic offsets even if it is much smaller than the whole galaxy photometric sample.…”
Section: Correction Of Systematic Offsetsmentioning
confidence: 99%
“…Additional details about the spectroscopic quality flags and their probability of being robust are given in Lilly et al (2009, see their Table 1). In addition to the confidence classes described in Lilly et al (2007), a decimal place (from 5 to 1, see Table 3 in Lilly et al 2009) in the class is added to indicate the level of consistency between the spectroscopic and photometric redshifts obtained by the Zurich Extragalactic Bayesian Redshift Analyzer (ZEBRA; Feldmann et al 2006), using the optical to infrared SED.…”
Section: Cosmos and The Bright 10k Zcosmos Spectroscopic Samplementioning
confidence: 99%
“…Rest frame absolute magnitudes have been computed from the best fitting template normalized to each galaxy photometry and redshift, using the code ZEBRA (Feldmann et al 2006). The template set is composed by six observed galaxy spectra (four from Coleman et al 1980 and two from Kinney et al 1996).…”
Section: Galaxy Propertiesmentioning
confidence: 99%